Everything you need to know about science homework - Zeman, Anne, frey50; Kelly, Kate. (New York : Scholastic Reference, 1997)
Provides fourth to sixth grade students and their parents with the information they need to complete science homework.
What's life all about? -- Animal kingdom -- Plant kingdom -- Ecology and the landscapes of life -- Planet Earth -- Outer space -- Physical world.
"An Irving Place Press book."
"In collaboration with UFT Dial-A-Teacher"--Cover.
Includes index.
Keywords: Science -- Study and teaching; Homework; Science; Homework